Integration of Social Accounting: The Effectiveness of Waste Management at the Evergreen Waste Bank, Kupang City - Wizaldy Fabiano Hilnicputro; Fransiskus Marlon Reu; Martina Kaisriani Rupa (International Journal of Economics and Management Research, 2025)
This study explores the integration of social accounting principles within community-based waste management practices at the Evergreen Waste Bank in Kupang City, East Nusa Tenggara, Indonesia. The research object focuses on the role of social and environmental accountability in improving the effectiveness of waste management systems at the grassroots level. Kupang City faces a persistent waste crisis, generating approximately 233 tons of waste per day, with only a small portion recycled effectively. This study addresses the problem of limited community participation, operational inefficiencies, and weak institutional support in local waste management initiatives. The research aims to evaluate how social accounting, when integrated with the 3R (Reduce, Reuse, Recycle) approach, can enhance environmental sustainability and socio-economic empowerment. Employing a qualitative phenomenological method, data were collected through in-depth interviews, field observations, and document analysis. Thematic analysis identified four key themes: (1) social awareness and environmental responsibility, (2) operational and technological challenges, (3) socio-economic empowerment through waste valorization, and (4) institutional and policy support. The findings reveal that the Evergreen Waste Bank contributes not only to waste reduction but also to local economic development and environmental education. However, its impact is constrained by manual data management and limited collaboration with local authorities. Synthesizing these results suggests that social accounting fosters transparency, accountability, and collective responsibility in environmental management. The study concludes that integrating social accounting into waste bank operations strengthens both community engagement and environmental governance. It recommends digital transformation, enhanced policy collaboration, and capacity-building initiatives to scale the model sustainably across Indonesian urban contexts.